Thermoplastic electrodes for detection of biomarkers - McCord, Cynthia P., author; Henry, Charles S., advisor; Reynolds, Melissa M., committee member; Neilson, James R., committee member; Bark, David L., Jr., committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: composite electrodes; immunoassay; biosensor; voltammetry; electrode materials